What happens for informal caregivers during transition to increased levels of care for the person with dementia? A systematic review protocol - Marianne Cranwell; Anna Gavine; Linda McSwiggan; Timothy B. Kelly (Systematic Reviews, 2018)
Abstract Background Dementia is a globally prevalent disease that requires ongoing and increasing levels of care, often provided in the first instance by informal caregivers. Supporting transitions in informal caregiving in dementia is a pertinent issue for caregivers, care providers and governments. There is no existing systematic review that seeks to identify and map the body of literature regarding the review question: ‘What happens for informal caregivers during transition to increased levels of care for the person with dementia?’ Methods/design ASSIA, CINAHL+, MEDLINE, PsycINFO, SCIE, Social Service Abstracts and Web of Science will be systematically searched. Specialist dementia research libraries will be contacted. Reviews identified as relevant during the search process, their reference lists, and reference lists of accepted papers will be hand-searched. Qualitative, quantitative and mixed methods studies that seek to represent the experiences of, or examine the impact upon, informal caregivers during transition to increased formal care for the person with dementia will be eligible for inclusion. Synthesis will be segregated into qualitative and quantitative papers. Findings will be summarised, and the review will be prepared for publication. Discussion The review will seek to identify potentially vulnerable groups in need of support and as such, inform the practice of those offering support. It will also inform future research by highlighting areas in which current literature is insubstantial. Systematic review registration PROSPERO CRD42017067248